The devil is a part-timer! 3 - Wagahara, Satoshi (Yen Press, Hatchette Book Group, 2015)
"Speak of the devil, and he'll fry you a burger! Sadao Maou, (aka Satan, the Devil King) has been relegated to flipping burgers at a MgRonald in suburban Tokyo. His greatest challenge so far, though, comes when a Sentucky Fried Chicken opens up across the street. Maou once led the forces of darkness, but can he triumph over the forces of chicken? And the new girl next door seems awfully polite and proper, almost as if she were hiding something..."--Back cover.